Association of Disease Activity and Disability With Rehabilitation Utilization in African American Adults With Rheumatoid Arthritis. Issue 1 (30th December 2021) - Thoma, Louise M.; Cleveland, Rebecca J.; Jonas, Beth L.; Bridges, S. Louis; Callahan, Leigh F.
Abstract : Objective: To examine the association of disease activity and disability with rehabilitation utilization in African American adults with rheumatoid arthritis (RA). Methods: We analyzed cross‐sectional baseline data from the Consortium for the Longitudinal Evaluation of African Americans with RA (CLEAR) I and CLEAR II registry. Disease activity was quantified with the Disease Activity Score in 28 joints using the C‐reactive protein level. Disability was measured with the Health Assessment Questionnaire. Rehabilitation utilization was determined by self‐reported recall of physical therapy or occupational therapy visits in the prior 6 months or ever. We examined the association of disease activity and disability with rehabilitation utilization using separate binary logistic regression models to estimate odds ratios and 95% confidence intervals and adjusted for potential confounders. We repeated the analyses with the sample stratified by disease duration (early RA and established RA). Results: Of 1, 067 participants, 14% reported utilizing rehabilitation in the prior 6 months, and 41% reported ever utilizing rehabilitation. Rehabilitation utilization in the prior 6 months was similar among those with early and established RA (12% versus 16%). A greater proportion of those with established RA reported any past rehabilitation utilization (28% versus 50%). Among those with established RA but not early RA, worse disability was associated with rehabilitation utilization in the prior 6 months. Disease activity was not associated with either outcome. Conclusion: Among African American adults with RA, rehabilitation utilization in the 6 months prior to assessment was low and associated with disability but not disease activity. Factors driving rehabilitation utilization are unclear.